Commercialisation of Food Crops and Farm Productivity: Evidence from Smallholders in Central Africa. Issue 4 (1st October 2016) - Ochieng, Justus; Knerr, Beatrice; Owuor, George; Ouma, Emily
ABSTRACT: Commercialisation of agriculture has long been considered an important driver of intensification, production, food security and farm incomes in Africa. This article investigates whether commercialisation is able to increase the intensification and yield of banana and legumes in central Africa. The study utilises survey data from 480 smallholder farmers in selected regions in rural Rwanda and the Democratic Republic of Congo (DRC). The findings show a positive effect of commercialisation on improved seed varieties use and food crop yields, even after controlling for an endogeneity problem. There is no strong evidence of commercialisation effect on fertilizer use among the sampled farm households. Apart from commercialisation, better education, larger farm sizes, access to markets and credit facilities, good roads and extension contacts are necessary for farmers to increase input use and crop yields. Overall, these findings suggest that programmes targeting to increase smallholder farm productivity through commercialisation will only work if they consider production and marketing conditions surrounding the target households.